2003
DOI: 10.1002/ppul.10391
|View full text |Cite
|
Sign up to set email alerts
|

Transition programs in cystic fibrosis centers: Perceptions of team members

Abstract: We previously surveyed cystic fibrosis (CF) center directors and adult patients with CF to assess their perceptions regarding transition from a pediatric to an adult setting. An important finding in those studies was a lack of standard programs for transfer of young adults with CF from pediatric to adult care settings. Patients with CF typically receive care from clinics utilizing a multidisciplinary approach, suggesting that every member of the CF team can impact the transition process. Our purpose in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 8 publications
2
56
0
Order By: Relevance
“…8 It is unclear as to whether this is also true for additional diseases or conditions, although other articles cite nurses as being in the best position to successfully coordinate transition efforts. 7,9 Articles addressing the concerns of providers suggest that pediatricians have apprehensions regarding the care their former patients may receive in an adult care setting. 9 Adult providers also were found to express concern about providing care to patients with conditions for which they may be unfamiliar in treating.…”
Section: Provider Roles and Responsibilitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…8 It is unclear as to whether this is also true for additional diseases or conditions, although other articles cite nurses as being in the best position to successfully coordinate transition efforts. 7,9 Articles addressing the concerns of providers suggest that pediatricians have apprehensions regarding the care their former patients may receive in an adult care setting. 9 Adult providers also were found to express concern about providing care to patients with conditions for which they may be unfamiliar in treating.…”
Section: Provider Roles and Responsibilitiesmentioning
confidence: 98%
“…7 Another article comparing providers who care for patients with sickle cell disease found that of the many potential health care providers, nurse practitioners were more likely to provide services associated with transitioning care. 8 It is unclear as to whether this is also true for additional diseases or conditions, although other articles cite nurses as being in the best position to successfully coordinate transition efforts.…”
Section: Provider Roles and Responsibilitiesmentioning
confidence: 98%
“…The time of transition to an adult CF center is 16-18 years of age but should be flexible, reflecting the adolescent's social maturity and health status. To guarantee a lifetime continuity of care there must be a close cooperation between the pediatric and adult units including the development of treatment guidelines [31,32].…”
Section: Transitional Carementioning
confidence: 99%
“…[59][60][61] Nonadherence to treatment remains a significant problem, particularly in the pediatric population. [62][63][64] Our study suggests that this may result from self-consciousness and striving to appear normal, engaging in risk-taking behaviors to gain a sense of control and independence, needing to "escape" the illness and exhaustion from the demands of treatment, and a sense of disempowerment.…”
Section: Figurementioning
confidence: 99%